MY SAY: The economic of rubber genome research - Abd Razak, Dzulkifli (2011)

(untitled)
Rubber, which has been synonymous with the Malaysian economy for a very long time, is now being overshadowed by oil palm. Its export earnings, including from rubber wood products, account for less than 5% of national export earnings. This can be enhanced if Malaysia develops superior scientific and technical expertise in the crop through the use of genomic research, discovering novel knowledge to move the industry up the value chain.